2004
DOI: 10.1093/carcin/bgh136
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of an isothiocyanate metabolite from cruciferous vegetables inhibits growth of human prostate cancer cell xenografts by apoptosis and cell cycle arrest

Abstract: Epidemiological surveys indicate that intake of cruciferous vegetables is inversely related to prostate cancer incidence, although the responsible dietary factors have not been identified. Our studies demonstrated that exposure of human prostate cancer cells in culture to the N-acetylcysteine (NAC) conjugate of phenethyl isothiocyanate (PEITC-NAC), the major metabolite of PEITC that is abundant in watercress, inhibited proliferation and tumorigenesis. The PEITC-NAC is known to mediate cytoprotection at initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
80
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 21 publications
6
80
0
Order By: Relevance
“…Our lab has reported that phenethyl isothiocyanate and sulforaphane induce growth arrest and apoptosis in prostate cancer cells in culture, as well as in xenografted tumors in immunodeficient mice, suggesting that they act also at the post-initiation progression stages (8,9). Isothiocyanates have been further reported to induce JNK-MAP kinases, p53-mediated apoptosis and cdk-mediated cell cycle arrest in different types of cancer cells (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Our lab has reported that phenethyl isothiocyanate and sulforaphane induce growth arrest and apoptosis in prostate cancer cells in culture, as well as in xenografted tumors in immunodeficient mice, suggesting that they act also at the post-initiation progression stages (8,9). Isothiocyanates have been further reported to induce JNK-MAP kinases, p53-mediated apoptosis and cdk-mediated cell cycle arrest in different types of cancer cells (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…They can act in a chemopreventive capacity via inhibition of carcinogen-activating phase I enzymes (1) and induction of phase II detoxification enzymes (2). Isothiocyanates are also active in the post-initiation phase of tumorigenesis and are, therefore, proposed to have chemotherapeutic potential (3,4). Isothiocyanate-mediated disruption of cancer progression is achieved by a variety of mechanisms including modulation of cell growth (5), inhibition of angiogenesis (6), suppression of metastasis (7), and induction of apoptosis (8,9).…”
mentioning
confidence: 99%
“…An amine linker was added to phenethyl isothiocyanate (PEITC) 3 without compromising cytotoxicity, and the molecule was immobilized to a solid phase resin. The pleiotropic cytokine macrophage migration inhibitory factor (MIF) was identified as a major biological target of PEITC.…”
mentioning
confidence: 99%
“…Antimutagenic and anticarcinogenic effects of PEITC are caused by the influence on a metabolic activation of mutagen by the inhibition of the level and/or activity of CYP enzymes and also by the effect on detoxification enzymes (15,29,40). PEITC has also the antiproliferative effect and induces apoptosis (24,41,42). Described bacteriotoxic effect of ITCs (24,43) suggests that the stimulation of apoptosis by chemopreventive agents may often reflect occurrence of toxic effects at high doses.…”
Section: Discussionmentioning
confidence: 99%